Pluralisme Agama dalam Pemikiran Syekh Siti Jenar - Otoman, Otoman (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2020)
This article discusses the roots of religious pluralism of Sheikh Siti Jenar. As one of theprosecution of Islam in the land of Java, he had a thought of religious pluralism, which is themeeting point of religions on the esoteric landscape (the transcendent unity of religions), in termsof Islamic mysticism known as Wahdat al-Adyan. The author deliberately used pluralism touncover the thoughts of Sheikh Siti Jenar based on his teachings. The theory of religiouspluralism classification, which includes secular humanism, global theology, syncretism, andlasting wisdom, is used to determine the pattern of religious pluralism found in the thought ofSheikh Siti Jenar. The problems discussed in this paper are the thoughts and patterns of religiouspluralism Sheikh Siti Jenar. For that purpose, the relevant data, obtained through the literaturestudy, is analyzed using a method of content analysis and descriptive-analytic. Based on thestudy conducted, it can be suggested that the concept of religious pluralism Sheikh Siti Jenar isthe implications of the plurality of scientific networks that accumulate in the developedteachings, Manunggaling Kawulo Gusti. The pluralism in the thought of Sheikh Siti Jenarcovered the meeting point of various religions at the esoteric level, because the difference forhim only occurred at the level of exoscorers alone. This view when associated with religiouspluralism classification belongs to the category of eternal wisdom. The thought of Sheik SitiJenar about the mystical maqamat in the process of discovering identity, the three elements thatbuild human beings, heaven and hell, and his views on nature, all of which are intertwined withthe teachings of Islamic mysticism, Hinduism, Buddhism and Javanese philosophy. The thoughtof Sheikh Siti Jenar took the pattern of religious pluralism, syncretism.